2006
DOI: 10.1007/bf02708470
|View full text |Cite
|
Sign up to set email alerts
|

Tuning size and catalytic activity of nano-clusters of cobalt oxide

Abstract: Cobalt oxides were prepared by three different methods: (1) by reacting cobalt nitrate with oxalic acid, (2) co-precipitating cobalt nitrate with sodium carbonate, and (3) using sodium dodecyl sulphate as organic surfactant. All three samples were characterized before and after calcination by solvent extraction and the resulting products examined by IR spectroscopy. In the case of method 3, the removal of surfactant was followed by TGA studies. Products from all three methods were identified by XRD. Peaks in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 27 publications
3
12
0
Order By: Relevance
“…The average particle size calculated with the help of Debye-Scherrer equation was found to be 50 nm. It was observed that the peak intensity increases with a narrowing down particle size distribution with high purity on calcination [13]. The EDX supports the formation of CoO nanoparticle with a chemical composition in the ratio of 1 : 1 as supported by TEM and SAED technique which supports the presence of good compositional homogeneity in the nanoparticles.…”
Section: X-ray Diffractionsupporting
confidence: 56%
“…The average particle size calculated with the help of Debye-Scherrer equation was found to be 50 nm. It was observed that the peak intensity increases with a narrowing down particle size distribution with high purity on calcination [13]. The EDX supports the formation of CoO nanoparticle with a chemical composition in the ratio of 1 : 1 as supported by TEM and SAED technique which supports the presence of good compositional homogeneity in the nanoparticles.…”
Section: X-ray Diffractionsupporting
confidence: 56%
“…The FT-IR spectra revealed the characteristic absorption peaks for metal-oxygen bonding and oxygen-hydrogen bonding. The peaks around n1 (451 cm À1 ) and n2 (584 cm À1 ) are originating from the stretching vibrations of the metal-oxygen bond characteristic of the spinel metal oxide [16]. The absorption peaks at n3 (1450 cm À1 ), n4 (1605 cm À1 ) and n5 (3437 cm À1 ) are assigned to the bending vibration of NH 4 , bending vibration of molecular water and OH-stretching vibration, respectively [17,18].…”
Section: Ft-ir Studiesmentioning
confidence: 98%
“…The peaks around 5 (3315.74 cm −1 ) and 3 (1600.97 cm −1 ) are assigned to O-H stretching and bending modes of water, respectively [23]. The peaks around at 2 (599.88 cm −1 ) and 1 (399.49 cm −1 ) are due to the stretching vibrations of the metal-oxygen bond characteristic of the metal oxide [24]. The absorption peaks at 8 (667.79 cm −1 ) and 7 (578 cm −1 ) are assigned to the (Co-O) modes [25], and peak 6 (393.49 cm −1 ) assigned from stretching vibration of the metal-oxygen bond characteristics of the spinal metal oxide.…”
Section: Structural Analysismentioning
confidence: 99%